Knitting Kauniyah and Qauliyah Verses: A Countenance Evaluation Study of the Trensains Program at Muhammadiyah Sragen Senior High School - Rachmaningtyas, Nur; Khoiruddin, Azaki; Cahyo Adi Kistoro, Hanif (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
Evaluative research is urgently needed to illustrate how Trensains is implemented in real-world contexts, particularly in educational institutions such as Muhammadiyah Senior High School in Sragen, which has adopted this approach. This study presents a unique approach by examining the integration of verses from kauniyah (the universe) and qauliyah (revelation/the Qur'an) in science learning. This study's novelty lies in applying the Countenance Stake evaluation model to assess the level of integration of Islamic values within the Trensains curriculum structure, which also represents a new contribution to the field of evaluating integrative science-based Islamic education. This research is an evaluative study with a descriptive-qualitative approach. The Countenance Evaluation Model developed by Stake was used to evaluate the program. The research location was Muhammadiyah Senior High School in Sragen, Central Java. This model examines program implementation through three main components, namely: (a) antecedents or initial context evaluation; (b) transactions that reflect the learning implementation process; and (c) outputs that evaluate the results of the process. The number of respondents was five teachers and three students. Implementing the Trensains program, which integrates science and divine revelation values, has significantly shaped students' conceptual understanding, analytical skills, and spiritual awareness. The learning strategy applied has led to a holistic scientific-spiritual approach. However, in its implementation, there are several obstacles, especially in the form of integration in the curriculum, especially in both fields, and strengthening the role of teachers as facilitators of integrated learning. Training in the integration of science and divine revelation values that is running has not been fully optimal due to limited understanding of the integrative approach, according to the field being developed, the lack of a comprehensive assessment rubric, and the lack of systemic support in terms of facilities and cross-subject collaboration.